SAT0294 IL33 ACTIVATES FIBROBLASTS AND INDUCES SKIN FIBROSIS IN SYSTEMIC SCLEROSIS. (2nd June 2020) - Wu, X.; Ming, B.; Dong, L.
Abstract : Background: Systemic sclerosis (SSc) is a chronic immune-mediated autoimmune disease that is characterized by fibrotic changes of the skin and internal organs, which in turn leads to distortion of tissue structure and gradual loss of organ function. So far, there is still no treatment allows full recovery from this severe disorder. Therefore, it is of great social significance to study the pathogenesis of this disease and find new targets for treatment. Interleukin 33 (IL-33), which is a potent inducer of type 2 immune response, has been confirmed to be involved in the development and progression of multiple fibrotic diseases. However, the role and mechanism of IL-33 in SSc-related fibrosis remains unclear. Objectives: To clarify the role of interleukin 33 (IL-33) and its receptor Suppression of tumorigenicity 2 (ST2) in the skin fibrosis of SSc, so to provides a new target for the treatment of fibrosis in patients with SSc. Methods: The levels of IL-33 and ST2 was analysed in human samples, murine models of SSc and in cultured fibroblasts by immunohistochemistry and immunofluorescence. The functional role of IL-33 was evaluated by detecting changes in proliferation, migration, and activation of fibroblasts stimulated with recombinant IL-33 protein. MAPK and NF-κB signallings of fibroblasts were assessed by western blotting and analyses of target genes. The role of IL-33 in skin fibrosis was analysed in IL-33 deficient mice (il33−/−) and wild-type controls injected with bleomycin or NaCl. Results: The expression of IL-33 and its receptor ST2 were up-regulated in skin lesions of SSc patients (Fig 1 A-C) and bleomycin-treated mice(Fig1 D-F). Compared to the healthy skin, the skin from SSc patients expressed more ST2 on fibroblasts membrane(Fig 1 B-C). IL33 induces MAPK and IκBα activation in human dermal fibroblast(Fig 2 A), and promote proliferation, migration and production of collagen of human dermal fibroblasts, but not the release of inflammatory factors(IL-6, MCP-1)(Fig2 B-G). Mice deficient for IL33 are protected from bleomycin-induced dermal fibrosis (Fig3). Conclusion: IL33 promotes skin fibrosis by activating fibroblasts, and IL33/ST2 may be an important target for the treatment of fibrosis in patients with SSc. References: [1]Ingegnoli F, Ughi N, Mihai C. Update on the epidemiology, risk factors, and disease outcomes of systemic sclerosis. Best practice & research. Clinical rheumatology. 2018;32(2):223-240. [2]Schmitz J, Owyang A, Oldham E, et al. IL-33, an interleukin-1-like cytokine that signals via the IL-1 receptor-related protein ST2 and induces T helper type 2-associated cytokines. Immunity. 2005;23(5):479-490. [3]Molofsky AB, Savage AK, Locksley RM. Interleukin-33 in Tissue Homeostasis, Injury, and Inflammation. Immunity. 2015;42(6):1005-1019. Disclosure of Interests: None declared